Family Business Succession Plan for Bumiputera-Owned Small and Medium Enterprises: A Review (Sains Humanika, 2023)
Transgenerational entrepreneurship is defined as the creative and initiative-taking creation of self-sufficiency in a family-owned business that lasts generations. The process of passing on management and ownership of a family business to the next generation through inheritance is known as family business succession. A succession plan is crucial for ensuring the company's transition and continuity. The process of selecting a replacement in a small and medium enterprise (SME) is more difficult because the number of successor candidates is smaller than in a corporate firm. Therefore, the purpose of this study is to identify the challenges and factors that incumbents must consider when selecting a successor and implementing a succession plan. The study's findings indicate that internal conflicts between the leader's business and family, the leader's obsession with his leadership legacy, and the successor's level of willingness to accept responsibility are the main obstacles to implementing a succession plan. The succession planning process considers a variety of factors, including education, competencies, demographic factors, relationships with family members and incumbents, experience, integrity, birth order, and primogeniture.
Keywords: Family-owned business, succession plan, succession challenges, succession factors, successor, incumbent